PC-12 Cell Line as a Neuronal Cell Model for Biosensing Applications - Daniela Oprea; Caroline G. Sanz; Madalina M. Barsan; Teodor Adrian Enache (Biosensors, 2022)
PC-12 cells have been widely used as a neuronal line study model in many biosensing devices, mainly due to the neurogenic characteristics acquired after differentiation, such as high level of secreted neurotransmitter, neuron morphology characterized by neurite outgrowth, and expression of ion and neurotransmitter receptors. For understanding the pathophysiology processes involved in brain disorders, PC-12 cell line is extensively assessed in neuroscience research, including studies on neurotoxicity, neuroprotection, or neurosecretion. Various analytical technologies have been developed to investigate physicochemical processes and the biosensors based on optical and electrochemical techniques, among others, have been at the forefront of this development. This article summarizes the application of different biosensors in PC-12 cell cultures and presents the modern approaches employed in neuronal networks biosensing.